Analysis of the Time of Dew Occurrence on the DCDB Panel at PLN GIS 150 kV Gunungsari Surabaya - Arum Vonie Rachmawati; Satya Cantika Agustinur; Rio Indralaksono; Kinanta Syahriannanda; I Made Niantara Riandana; Andu Mahdy Alim; Meta Yantidewi; Dzulkiflih Dzulkiflih (Berkala Sainstek)
The DCDB panel is a panel for distributing direct current electricity. Inside the panel there are cables to carry current which affects the temperature of the panel. The greater the current flowing, the greater the resulting temperature. Dew that occurs on the DCDB panel can cause various kinds of electrical disturbances, so the DCDB panel must be kept dry and protected from condensation. The dew parameter is the dew point. In order to minimize the occurrence of dew on the DCDB panel, it is necessary to know the prediction or estimate of the occurrence of dew on the DCDB panel by evaluating the Rectifier room temperature with the external environmental weather temperature. Therefore, research was carried out for 10 days in the PT. PLN (Persero) GIS 150 kV Gunungsari Rectifier room, Surabaya, which contained a DCDB panel. The data obtained is temperature monitoring data in the Rectifier room, DCDB panel body, and DCDB panel door. From this data, observations are made to see the temperature changes that occur in the panel. Environmental weather data is obtained via the Weather Underground website. The research data obtained was analyzed using RMSE and MAPE to check errors and graph plotting using SPSS. Based on the research conducted, it can be concluded that the dew point is estimated to occur at 03.30-05.00 in July with a temperature range of 21.3℃-23.3℃.